Potensi Mangrove sebagai Penunjang Ekowisata Bahari di Pantai Ketapang, Desa Batu Menyan, Kecamatan Teluk Pandan, Kabupaten Pesawaran, Provinsi Lampung - Anma Hari Kusuma (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Mangroves are high level plants that live on tropical coasts capable of adapting to salinity which is influenced by tides. Mangroves have ecological functions and economic functions. Ecological functions include protecting the shoreline, preventing seawater intrusion, habitat for various kinds of marine biota for feeding grounds, nursery grounds and spawning grounds in the waters. While the economic functions include as a tourist location, provider of food and medicine. Ketapang Beach is an area that has a mangrove ecosystem that can be used as a objects and attractions tourisme. The purpose of this study was to analyze the potential of mangroves as a support for marine ecotourism at Ketapang Beach. This research was conducted in September 2021. The research location was Ketapang Beach, Batu Menyan Village, Teluk Pandan District, Pesawaran Regency, Lampung Province. Analysis of the suitability of the mangrove ecotourism area at Ketapang Beach for all stations under conditional conditions. The carrying capacity of the area is 90 people per day. The carrying capacity of the utilization of as many as 9 people per day. Information about the condition and potential of the mangrove ecosystem on Ketapang Beach can be used to determine strategies for managing coastal and marine areas in a sustainable manner both for marine conservation and for the development of marine ecotourism.